Exploring the perspectives of new-in-practice specialists about the Health Advocate role: “I didn’t even know where to start” - Cochrane, Jacqueline Dorothy; Dudek, Nancy; Crawford, Kelsey; Cowley, Lindsay; LaDonna, Kori A (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Introduction: Current approaches to health advocate (HA) training leave many physicians feeling ill-equipped to advocate effectively. Likewise, faculty perceive the HA role as challenging to teach, role model, evaluate and assess. Progress on improving HA training is further stalled by debate over the role’s importance and whether it should be considered intrinsic to medical practice. Recent graduates are well-positioned to comment on how these challenges affect HA training and preparation for practice. Therefore, our purpose was to explore the perspectives of new-in-practice physicians who are keen to be effective advocates.Methods: Ten early-career physicians participated in semi-structured interviews exploring their perceived competence and motivation to engage in health advocacy. Constructivist grounded theory informed the iterative data collection and analysis process.Results: Participants wished they knew during training how much they would use advocacy in practice. While training imparted adequate patient-level advocacy skills, participants felt underprepared to enact system-level advocacy–which they conceptualized as a wide-range of activities including political advocacy. In turn, participants grappled with lack of preparation, waning motivation, feelings of futility, lack of value for advocacy and need for self-preservation. For these reasons, they questioned whether system-level advocacy should be expected of all physicians.Conclusions: Although training may adequately prepare physicians for patient-level advocacy, system-level advocacy training remains insufficient. While patient-level advocacy is integral to good care, whether system-level advocacy should be a universal expectation deserves closer consideration. Perhaps system-level health advocacy may be better conceptualized as a specialized role requiring additional training. Regardless, physician advocates’ efforts need to be valued for their contributions.